Dual role of protein tyrosine phosphatase 1B in the progression and reversion of non-alcoholic steatohepatitis - Águeda González-Rodríguez; M. Pilar Valdecantos; Patricia Rada; Annalisa Addante; Inés Barahona; Esther Rey; Virginia Pardo; Laura Ruiz; Laura M. Laiglesia; María J. Moreno-Aliaga; Carmelo García-Monzón; Aránzazu Sánchez; et al. (Elsevier, 2018)
Objectives: Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease in Western countries. Protein tyrosine phosphatase 1B (PTP1B), a negative modulator of insulin and cytokine signaling, is a therapeutic target for type 2 diabetes and obesity. We investigated the impact of PTP1B deficiency during NAFLD, particularly in non-alcoholic steatohepatitis (NASH). Methods: NASH features were evaluated in livers from wild-type (PTP1BWT) and PTP1B-deficient (PTP1BKO) mice fed methionine/choline-deficient diet (MCD) for 8 weeks. A recovery model was established by replacing MCD to chow diet (CHD) for 2-7 days. Non-parenchymal liver cells (NPCs) were analyzed by flow cytometry. Oval cells markers were measured in human and mouse livers with NASH, and in oval cells from PTP1BWT and PTP1BKO mice. Results: PTP1BWT mice fed MCD for 8 weeks exhibited NASH, NPCs infiltration, and elevated Fgf21, Il6 and Il1b mRNAs. These parameters decreased after switching to CHD. PTP1B deficiency accelerated MCD-induced NASH. Conversely, after switching to CHD, PTP1BKO mice rapidly reverted NASH compared to PTP1BWT mice in parallel to the normalization of serum triglycerides (TG) levels. Among NPCs, a drop in cytotoxic natural killer T (NKT) subpopulation was detected in PTP1BKO livers during recovery, and in these conditions M2 macrophage markers were up-regulated. Oval cells markers (EpCAM and cytokeratin 19) significantly increased during NASH only in PTP1B-deficient livers. HGF-mediated signaling and proliferative capacity were enhanced in PTP1BKO oval cells. In NASH patients, oval cells markers were also elevated. Conclusions: PTP1B elicits a dual role in NASH progression and reversion. Additionally, our results support a new role for PTP1B in oval cell proliferation during NAFLD. Keywords: PTP1B, Steatosis, Steatohepatitis, Inflammation, Oval cells